The Forms of Recognition of State Borders After World War II (With Particular Focus on the Arrangements Pertaining to the Polish-German Border) - Klafkowski, Alfons (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2021)
The paper is an English translation of Forma uznania granic państwowych po drugiej wojnie światowej, by Alfons Klafkowski, published originally in Polish in „Życie i Myśl” in 1964. The text is published as a part of a jubilee edition of the “Adam Mickiewicz University Law Review. 100th Anniversary of the Department of Public International Law” devoted to the achievements of the representatives of the Poznań studies on international law.